The Analysis of Illocutionary Speech Act on Boris Johnson’s Speeches about Covid-19 Pandemic - Kevin Sandi Sanusi; Weningtyas Parama Iswari; Satyawati Surya (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2022)
This study analyzes the types and functions used by Boris Johnson in his speech about COVID-19 pandemic. In education, this can help students to learn how to express something in English. The researcher uses five speeches that was conducted by Boris Johnson from 23 March 2020 to 31 October 2020. The researcher uses content analysis method on qualitative approach to describe and analyze the illocutionary act performed by Boris Johnson and then classifies them according to Searle’s theory of illocutionary act. The result is that Boris has performed 160 representatives illocutionary act, 48 directives, 54 comissives, 49 expressives, and 14 declaratives. As for the illocutionary act performed by Boris, he has performed 158 collaborative function, 118 convivial function, 46 competitive, and just 2 conflictive.